Morphological and Immunophenotypic Analysis in Diagnosis of Acute Leukaemia - Nurunnabi, Md; Mamdu, Mosammath Khadiza; Siddika, Ayesha; Zafreen, Farzana; Wahab, Md Abdul; Shermin, Shahana (Delta Medical College Journal, 2022)
Background: Leukaemias are neoplastic proliferations of haematopoietic stem cells and form a major proportion of haematopoietic neoplasms that are diagnosed worldwide. Objective: To differentiate between morphological and immunophenotypic analysis in the diagnosis of acute leukemia. Materials and method: This cross sectional study was conducted in the department of Haematology, Armed Forces Institute of Pathology (AFIP), Dhaka, Bangladesh from January 2008 to December 2008. Total 50 patients were included after fulfilling inclusion and exclusion criteria. Results: The total of 50 bone marrow samples from suspected cases of acute leukaemia were included in the study. Out of 50 samples, 48 cases were diagnosed as either acute myeloid leukaemia (19 or 38%) or acute lymphoblastic leukaemia (29 or 58%) and 02 (04%) cases were morphologically indistinguishable. All 50 cases were subjected to immunophenotypic study. Out of 50 cases immunophenotypically 14(28%) were acute myeloid leukaemia (AML), 32(64%) were acute lymphoblastic leukaemia (ALL), and bi-phenotypic leukaemia and acute undifferentiated leukaemia were 02(04%) each. In this study Male: Female ratio was 1.3:1. Out of 19(38%) cases of AML, 29(58%) cases of ALL and 02(04%) cases of indistinguishable diagnosed morphologically, 14(28%) were found to be AML, 32(64%) ALL, 02(04%) bi-phenotypic and 02(04%) were acute undifferentiated leukaemias on immunophenotyping respectively. Out of 29 cases identified as ALL on morphology 25(86.2%) were confirmed as ALL, 02(07%) turned out to be AML, 01(3.4%) was bi-phenotypic and 01(3.4%) was undifferentiated. Conclusion: In this study, acute lymphoblastic leukaemia was the commonest type of leukemia followed by acute myeloid leukaemia with male predominance seen in all types of leukaemia. Delta Med Col J. Jul 2020 8(1): 15-20